2001
DOI: 10.1086/322358
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous X‐Ray Pulsars and Soft Gamma‐Ray Repeaters in Supernova Remnants

Abstract: I consider the state of play regarding associations of supernova remnants (SNRs) with anomalous X-ray pulsars (AXPs) and soft gamma-ray repeaters (SGRs). The three AXP/SNR associations are convincing, and are consistent with AXPs being young, low-velocity neutron stars. The three SGR/SNR associations are far more likely to be chance superpositions, and rely on SGRs being high velocity (>1000 km s −1 ) objects. These results imply either that AXPs evolve into SGRs, or that SGRs and AXPs represent different popu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
218
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(230 citation statements)
references
References 115 publications
12
218
0
Order By: Relevance
“…Halpern et al (2005) discovered transient radio emission from the transient AXP XTE J1810-197 which appeared sharply modulated at the rotation period with peak flux densities >1 Jy (Camilo et al 2006), orders of magnitude brighter than the reported upper limits for this or any other AXP. Gaensler et al (2001) have observed 4U 0142+61 with the VLA (1.4 GHz), but only a 5σ upper limit of 0.27 mJy could be extracted from the data.…”
Section: Introductionmentioning
confidence: 93%
“…Halpern et al (2005) discovered transient radio emission from the transient AXP XTE J1810-197 which appeared sharply modulated at the rotation period with peak flux densities >1 Jy (Camilo et al 2006), orders of magnitude brighter than the reported upper limits for this or any other AXP. Gaensler et al (2001) have observed 4U 0142+61 with the VLA (1.4 GHz), but only a 5σ upper limit of 0.27 mJy could be extracted from the data.…”
Section: Introductionmentioning
confidence: 93%
“…GögüY et al (2001 suggested that the difference between these values for the two SGRs is a result of a difference in an intrinsic physical property of the sources, such as the strength of magnetic field or the size of the active region. Given the generally softer persistent emission spectra of AXPs compared to SGRs, as well as the less frequent outbursts of the AXPs, it is reasonable to suspect that the two source classes also differ by some physical property; age (Kouveliotou et al 1998;Gaensler et al 2001), magnetic field , and progenitor mass (Gaensler 2004) have been proposed. The similarity of the burst durations of all three sources implies, however, that the physical property resulting in different mean burst durations must be different from the one that results in different average spectra and outburst frequency.…”
Section: Similarities Between Axp and Sgr Burstsmentioning
confidence: 99%
“…4 we have drawn the spectral energy density of AXP 4U 0142+61 from radio (VLA, <0.27 mJy at 5σ Gaensler et al 2001) to X-ray (ASCA, White et al 1996). Both observed and dereddened fluxes are shown, using a reddening of 5.1 mag as derived from the X-ray absorption.…”
Section: The Spectral Energy Densitymentioning
confidence: 99%
“…Two of the five sources are associated with supernova remnants (Gaensler et al 2001), indicating that AXPs are young objects. For none of the sources, there is any evidence for orbital motion (from timing, e.g., Wilson et al 1999;Mereghetti et al 1998).…”
Section: Introductionmentioning
confidence: 99%